The Effect of the Presence of Cu2+ and Fe3+ Metal Ions on the Sorption of Mercuric Ion (Hg2+) by Sargassum cristaefolium - Alcantara, Rochelle T; Apodaca, Dahlia C.; Guzman, Manuel R De (ASEAN Journal of Chemical Engineering, 2007)
revious studies have indicated that the seaweed Sargassum cristaefolium is capable of binding with metal ions. The metal sorbing property of S. cristaefolium suggests its possible participation in the removal of Hg2+ ions in water and wastewater. However, the potential application of S. cristaefolium for environmental remediation and precious metals recovery depends on the understanding of the other factors that could play a role in the sorption process. This study illustrates the effects of some variables, such as pH and temperature, and that of the presence of other metal ions on the sorption process involving the binding of Hg2+ ions to S. cristaefolium. The uptake of Hg2+ ion was found to be affected by the initial concentration and the charge densities of the competing ions. Cu2+ ion shows a stronger affinity to Sargassum in the three metal systems of Hg2+, Cu2+, and Fe3+ ions. On the other hand, results show that Fe3+ ion is not a potential competitor for binding sites considering that no Fe3+ ion uptake by Sargassum has been observed.